Sanjha Punjab – United Punjab: Exploring Composite Culture in a New Zealand Punjabi Film Documentary - Brown Pulu, TJ; Mukhtar, A; Singh, H (University of Otago Library, 2019)
This paper examines the third author’s positionality as the researcher and storyteller of a PhD documentary film that will be shot in New Zealand, Pakistan, and North India. Adapting insights from writings on Punjab’s composite culture, the film will begin by framing the Christchurch massacre at two mosques on 15 March 2019 as an emotional trigger for bridging Punjabi migrant communities in South Auckland, prompting them to reimagine a pre-partition setting of “Sanjha Punjab” (United Punjab). Asim Mukhtar’s identity as a Punjabi Muslim from Pakistan connects him to the Punjabi Sikhs of North India. We use Asim’s words, experiences, and diary to explore how his insider role as a member of these communities positions him as the subject of his research. His subjectivity and identity then become sense-making tools for validating Sanjha Punjab as an enduring storyboard of Punjabi social memory and history that can be recorded in this documentary film.
Keywords: Sanjha Punjab; United Punjab; Composite culture; Punjabis; Pakistani; Hindustani; Muslims; Sikhs; South Auckland